2013
DOI: 10.1111/jhn.12052
|View full text |Cite
|
Sign up to set email alerts
|

British Dietetic Association evidence‐based guidelines for the protein requirements of adults undergoing maintenance haemodialysis or peritoneal dialysis

Abstract: Evidence suggests that nutritional status may be maintained with lower protein intakes than previously recommended. However, the evidence base is limited and further randomised controlled trials are required to establish the optimal protein intake for dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 37 publications
2
51
0
1
Order By: Relevance
“…As far as the quality of protein intake is concerned, it is noteworthy that more than 50% of dietary protein consumed by our patients was of animal origin. This finding is in line with the recommendations [20,22], although some authors believe more evidence is needed [30]. …”
Section: Discussionsupporting
confidence: 81%
“…As far as the quality of protein intake is concerned, it is noteworthy that more than 50% of dietary protein consumed by our patients was of animal origin. This finding is in line with the recommendations [20,22], although some authors believe more evidence is needed [30]. …”
Section: Discussionsupporting
confidence: 81%
“…It is clear that each DI study uses its own interpretation of body weight, which confounds comparison. 52 These differences in methodology make it hard to generalize findings; however, studies in both HD and PD patients show low DEI and DPI.…”
Section: Challenges Of DI Studiesmentioning
confidence: 97%
“…Naylor et al (2013) performed a literature review aiming to elaborate guidelines on the protein requirement of hemodialysis patients and concluded that the intake of 1.1 g/kg/day is able to meet their needs and avoid protein malnutrition. However, in this study protein intake was lower than this value, showing the need for intervention and nutritional orientation, since this intake, when insufficient, is related to higher mortality 15 . In the present study there was a statistically significant negative correlation (p = 0.02) between fat mass and protein intake (g/kg), indicating that the lower the protein intake, the greater the fat mass.…”
Section: Methods Of Nutritional Evaluation Between Patients In Hemodimentioning
confidence: 64%